2010
DOI: 10.2182/cjot.2010.77.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Mothering Occupations When Parenting Children with Feeding Concerns: A Mixed Methods Study

Abstract: Mixed methods data analysis revealed the complex nature of the interaction between mothering occupations and mothering a child with feeding concerns as well as how these concerns might influence occupational therapy practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…A recent review of the MMPR literature revealed that the concurrent model is relatively popular within MMPR (Mayoh & Onwuegbuzie, 2012). Within this model, phenomenological and complementary data are collected concurrently in order to cross-validate or to confirm findings (Patton, McIlveen, & Hoare, 2008;Winston, Dunbar, Reed, and Francis-Connolly, 2010). For example, during their research into mothering occupations, Winston et al (2010) collected data from mothers concurrently using the Parental Stress Scale (PSS; Berry & Jones, 1995), Life Satisfaction Index for Parents (LSI-P; Renwick & Reid, 1992), and phenomenological interviews.…”
Section: Phenmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of the MMPR literature revealed that the concurrent model is relatively popular within MMPR (Mayoh & Onwuegbuzie, 2012). Within this model, phenomenological and complementary data are collected concurrently in order to cross-validate or to confirm findings (Patton, McIlveen, & Hoare, 2008;Winston, Dunbar, Reed, and Francis-Connolly, 2010). For example, during their research into mothering occupations, Winston et al (2010) collected data from mothers concurrently using the Parental Stress Scale (PSS; Berry & Jones, 1995), Life Satisfaction Index for Parents (LSI-P; Renwick & Reid, 1992), and phenomenological interviews.…”
Section: Phenmentioning
confidence: 99%
“…Within this model, phenomenological and complementary data are collected concurrently in order to cross-validate or to confirm findings (Patton, McIlveen, & Hoare, 2008;Winston, Dunbar, Reed, and Francis-Connolly, 2010). For example, during their research into mothering occupations, Winston et al (2010) collected data from mothers concurrently using the Parental Stress Scale (PSS; Berry & Jones, 1995), Life Satisfaction Index for Parents (LSI-P; Renwick & Reid, 1992), and phenomenological interviews. They adopted a descriptive phenomenological approach that utilised member checks, where participants' transcripts were reviewed by the participants themselves to ensure they reflected their personal experiences, thereby increasing descriptive validity (Maxwell, 1992(Maxwell, , 2005.…”
Section: Phenmentioning
confidence: 99%
See 1 more Smart Citation
“…This purpose is parallel to triangulation outlined by Greene et al (1989) and involves convergence, corroboration, or correspondence of the results from the phenomenological and alternative methods. An example of confirmation is provided by Winston, Dunbar, Reed, and Francis-Connolly (2010) during their research into SURVEYING THE LANDSCAPE 21 mothering occupations that involved comparing phenomenological and questionnaire data through the development of matrices in order to cross-validate findings. They justified that the adoption of this approach would allow the results and discussion to focus on mixed analysis as opposed to analysing the data sets independently.…”
Section: Orientatingmentioning
confidence: 99%
“…This thesis is even more prominent within confirmation because the objective of phenomenological enquiry is relatively inflexible and rigid. Specifically, the essence of all phenomenological work is to explore the nature of human experience; therefore, it is difficult to see how this can be cross-validated-for example, using the Parental Stress Scale (PSS) and Life Satisfaction Index for Parents (LSI-P) within Winston et al's (2010) study.…”
Section: Orientatingmentioning
confidence: 99%